Lie as the anthropological destruction - Wyrostkiewicz, Michał (Bogoslovni vestnik, 2023)
The theory of post-truth and the conviction that absolute objective truth does not exist have many supporters in the modern world. A lie seen from this point of view appears to be one of the many ways people contact each other. The conducted research shows that this reasoning is incorrect. It proves that a lie is a reality that destroys those who have been lied to and those who are lying, as well as other people who are found in their environment. A lie drives people away from the truth, replacing it with untruth. In this way, it strikes a person and disturbs the order in one’s social environment. Thus, it becomes an anthropological destruction. This creates an “alternative world” that “competes” with God’s created world. Also, by rejecting God’s call to live according to the truth, man moves away from God and draws closer to Satan. The world “created” by a liar is not appropriate to human nature, it cannot become a space for his development, but is only regression and, consequently, destructive. The matter of lying and its consequences appear to be very topical today when the “power of disinformation” is being revealed more and more clearly
Keywords: anthropology; antropologija; communication; dezinformacija; disinformation; družbeno življenje; komunikacija; laž; lie; morala; morality; social life